Microstrip Yagi antenna’s design and analysis for wireless lan application / Nuraiza Ismail, Rina Abdullah and Suziana Omar - Ismail, Nuraiza; Abdullah, Rina; Omar, Suziana (2015)
The research focused on the design of microstrip antenna that will improve gain as the main goal in getting good antenna performance. This research presents the design and analysis of a new kind of Yagi array microstrip patch antenna which appropriate for wireless LAN application. The design is a derivative of the original microstrip Yagi antenna of two branches that comprises of two elements including driven and parasitic elements which consists of reflector and directors. The analysis has been carried out to identify the effect of adding another two more branches in comparison to the microstrip Yagi structure of one branch and two branches. The four branches of this microstrip Yagi antenna has been connected using two branches that are cooperated to each other in a composite array format using corporate-feed network. The proposed antenna design is fed by microstrip line that based on quarter wave impedance matching technique and simulated using Computer Simulation Tool (CST) Microwave Studio. The simulation result of return loss has shown the operated frequency at 5.6 GHz that is appropriate coverage standard of IEEE 802.11 in 5 GHz band between 5.15-5.875 GHz. The proposed four branches Yagi array of microstrip patch antenna can also achieve a gain above 10 dB and a high front-to-back (F/B) ratio as much as 13 dB.